2015
DOI: 10.1080/13607863.2015.1028332
|View full text |Cite
|
Sign up to set email alerts
|

Chinese version of the Aging Perceptions Questionnaire (C-APQ): assessment of reliability and validity

Abstract: The C-APQ could be a reliable and a valid measure of the self-perceptions of aging in the elderly in China, which may help to improve the life quality and extend longevity of the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Using the maximum likelihood and the varimax rotation, 4 factors were extracted that together explained 52.8% of the total variance. Similar results were reported by other investigators [12,32]. Also, Slotman et al, by conducting an EFA, confirmed the multidimensional factor structure of the APQ [10,14].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Using the maximum likelihood and the varimax rotation, 4 factors were extracted that together explained 52.8% of the total variance. Similar results were reported by other investigators [12,32]. Also, Slotman et al, by conducting an EFA, confirmed the multidimensional factor structure of the APQ [10,14].…”
Section: Discussionsupporting
confidence: 90%
“…Chen at al. assess the reliability of the Chinese version of the Questionnaire (C-APQ) and found acceptable alphas ranging from 0.665 to 0.869 for the subscales of the C-APQ [12]. Wang et al found a Cronbach's alpha of 0.87 for the APQ, indicating that the questionnaire had good consistency and reliability [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The Chinese version of APQ has been confirmed with cumulative variance contribution rate 65.27%, Cronbach's α coefficient 0.884 for the total scale. 34 Each dimension was calculated from the arithmetic mean of related items, with higher scores indicating greater endorsement of a specific perception.…”
Section: Assessment Of Spamentioning
confidence: 99%